Ergonomic analysis in small business jobs - Suntti, Carla (2023)
Abstract: In the context of the production system together with the basic principles of ergonomics in jobs, this article seeks to present a case study developed to evaluate the ergonomic conditions of workers in a semi-automated factory of cement artifacts such as block and interlocked pavement (paver). We seek to discuss how the lack of interaction in the design of projects contributes to the appearance of ergonomic problems caused to employees for the development of tasks. The aim of this study is a project to improve the conditions of jobs. This is a qualitative research explained in a case study, using theOvako Working posture Assessement System(OWAS) and NIOSH (National Joint Institute of Occupational Safety and Health) as a basis methods. With the  application of the methods, it was verified the need for corrective actions in the activities of raw material movement, palletization of material and collection of press material,aiming at the use of design requirements that allow the actors involved to develop changes that benefit the worker and qualify the form of production.